2019
DOI: 10.1155/2019/4715953
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Transport in the V-Shaped Edge Distorted Zigzag Graphene Nanoribbons with Substitutional Doping

Abstract: Density-functional theory (DFT) in combination with the nonequilibrium Green’s function formalism is used to study the effect of substitutional doping on the electronic transport properties of V-shaped edge distorted zigzag graphene nanoribbons (DZGNRs), in which DZGNRs with the various widths of four-, six-, and eight-zigzag chains are passivated by H atoms. In this work, Si atoms are used to substitute carbon atoms located at the center of the samples. Our calculated results have determined that Si can chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
1
1
0
1
Order By: Relevance
“…2, by the adsorption, the HOMO and LUMO energy levels were shifted and also the E g increased. The E g for our studied graphene was 2.00 eV, which is in good agreement with other previous studies [21,22]. By the substitution of one C atom by Al or Ga atom the E g decreases to 1.77 and For this con guration, adsorption process was studied for the mentioned doped sites and it was seen as the only adsorption from O atom of the water molecule.…”
Section: Adsorptionsupporting
confidence: 91%
“…2, by the adsorption, the HOMO and LUMO energy levels were shifted and also the E g increased. The E g for our studied graphene was 2.00 eV, which is in good agreement with other previous studies [21,22]. By the substitution of one C atom by Al or Ga atom the E g decreases to 1.77 and For this con guration, adsorption process was studied for the mentioned doped sites and it was seen as the only adsorption from O atom of the water molecule.…”
Section: Adsorptionsupporting
confidence: 91%
“…Những hiệu ứng vận chuyển điện tử, lượng tử do hiệu ứng giam cầm lượng tử bởi cấu trúc (Tien et al, 2016;Cywiński et al, 2018). Việc điều khiển các tính chất điện tử và phổ hấp thụ của các băng nano PG gần đây đã được thực hiện bằng cách sử dụng nhiều kỹ thuật thiết kế vật liệu có sự hỗ trợ của máy tính, chẳng hạn như pha tạp nguyên tử (Tien et al, 2019), tôi hóa biên (Tien et al, 2020) và hấp phụ vật lý và hóa học (Mi et al, 2020).…”
Section: đặT Vấn đềunclassified
“…In detail, GNRs, as one of the most brilliant ribbons, show either metallic or semiconducting properties according to their different edge configuration [10,11]. Recent studies have indicated that various methods, for instance, passivation, defect, substitution, external electric fields, and heterojunctions, may regulate the electronic and transmission properties of GNRs [12][13][14][15]; however, the zero band gap of graphene limits its application as a spintronic material [16][17][18]. Due to the existence of Dirac cones in the proximity of the Fermi level, the δ-graphyne NR (δGYNR) has similar electronic properties to the GNR [19].…”
Section: Introductionmentioning
confidence: 99%